Symptomatic or asymptomatic recurrence of ovarian cancer: does it influence survival?. Issue 8 (9th June 2022) - Madland, Karen; Bjorge, Line; Småstuen, Milada Cvancarova; Dørum, Anne; Vistad, Ingvild
Abstract : Objective: The survival benefit of monitoring CA125 in ovarian cancer patients after primary treatment is debated due to findings varying from insignificant survival differences to prolonged median overall survival in favor of asymptomatic patients. Hence we aimed to compare ovarian cancer patients with and without symptoms at the time of the first diagnosed recurrence in terms of post-recurrence survival and overall survival, and to explore time to recurrence and common symptoms at recurrence. Methods: We included 421 women with ovarian cancer from a prospective multi-institutional Norwegian study of first recurrence of gynecological cancer over the period from March 2012 to April 2016. Patients were interviewed by clinicians at participating hospitals, and patient reported and clinical variables were recorded in a standardized questionnaire. The Kaplan–Meier method and the multivariate Cox model were used to evaluate post-recurrence survival and overall survival. Results: Of the 406 patients included, 183 (45%) patients were diagnosed with asymptomatic recurrence, and 223 (55%) patients had symptoms at recurrence. Asymptomatic patients had their recurrence detected 2 months later than symptomatic patients (14 vs 12 months, respectively, p=0.17). Median post-recurrence survival was significantly longer in asymptomatic patients compared with patients with symptoms at recurrence (33.9 vs 26.2 months, respectively, p=0.002). The post-recurrence survival rate remained higher for symptomatic patients in the adjusted analysis (hazard ratio (HR)=1.42, p=0.001). Median overall survival was 47.8 months for asymptomatic patients versus 44.0 months for symptomatic patients in the unadjusted analyses (p=0.056). Asymptomatic patients had a significantly longer survival in the adjusted analysis (HR=1.24, p=0.046). Pain was the most common symptom at recurrence (54%). Conclusion: Patients with asymptomatic recurrence had a better prognosis based on post-recurrence data and the multivariate Cox regression analysis of overall survival. However, a closer exploration of differences in development of recurrence is needed as these results may give rise to more individualized follow-up for ovarian cancer patients.